2021
DOI: 10.1177/00469580211017666
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Increasing Physician Provision of Pre-Exposure Prophylaxis: Implications for Medical Student Training

Abstract: There is growing evidence that pre-exposure prophylaxis (PrEP) prevents HIV acquisition. However, in the United States, approximately only 4% of people who could benefit from PrEP are currently receiving it, and it is estimated only 1 in 5 physicians has ever prescribed PrEP. We conducted a scoping review to gain an understanding of physician-identified barriers to PrEP provision. Four overarching barriers presented in the literature: Purview Paradox, Patient Financial Constraints, Risk Compensation, and Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 63 publications
(140 reference statements)
1
12
0
Order By: Relevance
“…To meet the goal of ending the HIV epidemic, PrEP content should be taught in all medical schools. 25 We found in our survey that only 38% taught PrEP content at all. Further, given the disproportionate burden of HIV experienced by MSM, bi-sexual, and transgender populations, content should include this population prominently, and in our sample even fewer schools, 15.4%, reported teaching this content.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…To meet the goal of ending the HIV epidemic, PrEP content should be taught in all medical schools. 25 We found in our survey that only 38% taught PrEP content at all. Further, given the disproportionate burden of HIV experienced by MSM, bi-sexual, and transgender populations, content should include this population prominently, and in our sample even fewer schools, 15.4%, reported teaching this content.…”
Section: Discussionmentioning
confidence: 59%
“…A scoping review recently conducted by us identified lack of PrEP training in medical schools as one of the barriers to PrEP prescribing among physicians. 25 Lecture was reported as the most frequent method of teaching this content. Given our previous work on implicit bias, 26 it is clear that direct patient contact and simulations are needed to improve outcomes in work with LGBT patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 For example, CoP can be used to identify and develop primary care curriculum that introduces new teaching techniques. For instance, new models of training, including the use of audits and the patient-centered medical home, 9 - 11 are approaches that can be used to train medical students to prescribe PrEP 12 based on a patient’s risk and/or circumstance.…”
mentioning
confidence: 99%
“…PrEP guidelines, conferences, webinars, training modules, and public health detailing have improved HIV specialists’ and primary care providers’ knowledge of and willingness to prescribed PrEP [12,13]. Studies have shown that the number of HIV specialists and primary care providers who prescribe PrEP in the United States has risen steadily but remains insufficient [14,15]. Converting PrEP knowledge to discussion of PrEP with patients to prescription requires that providers discuss patients’ sexual practices, sexual health needs, and injection practices or other illicit drug use, conduct appropriate physical examinations and laboratory testing, navigate health insurance, and refer patients to other support services as needed [12,16].…”
mentioning
confidence: 99%